Spatial proximity as a factor in the selection of marriage - Yem, N B; Kudaibergenova, R (Journal of Oriental Studies, 2016)
For overseas Koreans the most important of marital selection, along with homogamy is spatial6 geographic proximity. It increases the probability of meeting with a partner who is more likely to resemble and social characteristics, including the similarity of values and interests. Long stay Korean ethnic communities in China, Japan, CIS is an exact proof that geographic proximity, the size of the ethnic group, as well as ethno-demographic heterogeneity led representatives of the Korean ethnic group geographically close choice of mirage partner.